Deforming D‐brane models on T6/(Z2×Z2M) orbifolds. Issue 4 (8th March 2016) - Koltermann, Isabel; Blaszczyk, Michael; Honecker, Gabriele
Abstract : We review the stabilisation of complex structure moduli in Type IIA orientifolds, especially on T 6 / ( Z 2 × Z 6 ′ × Ω R ) with discrete torsion, via deformations of Z 2 × Z 2 orbifold singularities. While D6‐branes in SO(2 N ) and USp(2 N ) models always preserve supersymmetry and thus give rise to flat directions, in an exemplary Pati‐Salam model with only U( N ) gauge groups ten out of the 15 deformation moduli can be stabilised at the orbifold point.